Karakteristik Manajemen Pendidikan Islam Pada Zaman Dinasti Abbasiyah - Irwansyah (STAI Terpadu Yogyakarta, 2023)
It is undeniable that civilization during the Abbasid Dynasty was the heyday of Islam with the development of education and science. The rapid development of education during the Abbasid Dynasty was due to the large number of Islamic educational institutions at that time. The characteristics of Islamic education management at that time were a benchmark of educational progress, so in this case a library research study was needed in describing the form of Islamic education management, this research is a type of library research research with data sources coming from library data from various books and articles published relevant to the object of research and data analysis is carried out by collecting raw data, data reduction, data display, and verification/conclusion. The characteristics of Islamic education management in the Abbasid dynasty have an inclusive character towards students from various ethnic backgrounds, races, religions and between groups, the existence of self-supporting education financing through waqf, participation and support of the caliphs to the world of education, high welfare of educators, facilities and adequate educational infrastructure. Based on the results of the study in the form of a description of the characteristics of Islamic education management during the Abbasid Dynasty, it can add to the repertoire of the realm of education management to improve the quality of education, especially in Indonesia.